Validity and Reliability of a Linear Position Transducer to Measure Velocity, Duration, and Displacement in the Barbell Back Squat - Ryan Gant; Anthony Pinzone; Jennifer Rivera; Edward Pelka; Emily Tagesen; Modesto Lebron; Adam Jajtner (International Universities Strength and Conditioning Association, 2023)
The purpose of this investigation was to determine the validity and reliability of the Humac360 linear position transducer (LPT) as compared to Tendo Weightlifting Analyzer. Seventeen recreationally active men and women completed three visits. Visit one included maximal strength assessments via one-repetition maximum (1RM) for the barbell back squat. On visits two and three, participants completed two sets of three repetitions at 30-, 50-, 60-, and 70% 1RM. Mean Concentric Velocity (MCV), Peak Velocity (PV), Displacement (D), and Duration (T) were collected. Repetition data agreement was assessed with Intraclass Correlation Coefficients (ICCs) and were categorized as poor (<0.50), moderate (0.50 - 0.75), good (0.75 - 0.90), and excellent (>0.90). Significance was accepted at an alpha (p) value < 0.05. Repetition-to-repetition comparisons between devices demonstrate varying degrees of agreement, with significant differences between devices across all intensities and all measurements (p < 0.001). Inter-set reliability was excellent for MCV, PV, D, and T with the exceptions of MCV and PV at 70% 1RM (ICC2,k = 0.548 and 0.816). Inter-session reliability data demonstrated reduced agreeableness in an intensity-dependent manner, with ICCs decreasing and SEMs increasing with increases in intensity. The Humac360 LPT does not appear to be valid when compared to the criterion reference, though we contend it maintains construct validity. Coaches may use the Humac360 LPT as a tool to monitor fatigue, and the associated changes in trainee movement velocity on an inter-set and inter-session basis.